Contraception for adolescents with chronic rheumatic diseases - Lourenço,Benito (2017)
ABSTRACT Contraception is an important issue and should be a matter of concern in every medical visit of adolescent and young patients with chronic rheumatic diseases. This narrative review discusses contraception methods in adolescents with juvenile systemic lupus erythematosus (JSLE), antiphospholipid syndrome (APS), juvenile idiopathic arthritis (JIA) and juvenile dermatomyositis (JDM). Barrier methods are safe and their use should be encouraged for all adolescents with chronic rheumatic diseases. Combined oral contraceptives (COC) are strictly prohibited for JSLE and APS patients with positive antiphospholipid antibodies. Reversible long-acting contraception can be encouraged and offered routinely to the JSLE adolescent patient and other rheumatic diseases. Progestin-only pills are safe in the majority of rheumatic diseases, although the main concern related to its use by adolescents is poor adherence due to menstrual irregularity. Depot medroxyprogesterone acetate injections every three months is a highly effective contraception strategy, although its long-term use is associated with decreased bone mineral density. COC or other combined hormonal contraceptive may be options for JIA and JDM patients. Oral levonorgestrel should be considered as an emergency contraception method for all adolescents with chronic rheumatic diseases, including patients with contraindication to COC.